THE KINETICS DEVOLOPMENT OF MARTENSITE DEFORMATION IN STAINLESS STEEL 12Cr18Ni10Ti IRRADIATED BY NEUTRON - Maksimkin, O. P.; Emelyanov, A. I.; Naltaev, A.; Berdalyev, D. T.; Rakhashev, B. K. (Recent Contributions to Physics, 2008)
The new results on reactor (WWR-K) irradiation on kinetic parameters of ’ martensitic transformation and true characteristic of strenghr and plasticity of 12Cr18Ni10Ti stainless steel were reported.
Keywords: WWR-K irradiation